2015
DOI: 10.1002/kin.20962
|View full text |Cite
|
Sign up to set email alerts
|

The Model of “Minimal Oscillator” Derived from the Kinetic Mechanism of the H2O2-NaSCN-NaOH-CuSO4Dynamical System

Abstract: Dissipative chemical reactions, which involve oscillatory variations of the concentrations of the intermediates in time, are usually characterized with complicated kinetic mechanisms. However, the essential source of the oscillations can often be reduced to only a few reaction steps providing the alternative domination of the positive and negative feedback loops. In an extreme case such a reduction leads to the so-called "minimal oscillator," the concept used in the past for the well-known Belousov-Zhabotinsky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The reaction Cu21 is taken from Refs. 16,20–22. The reactions Cu22 (red letters), T31 (red dotted arrow), and T32 (red solid arrow) are incorporated in the present work [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction Cu21 is taken from Refs. 16,20–22. The reactions Cu22 (red letters), T31 (red dotted arrow), and T32 (red solid arrow) are incorporated in the present work [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Discussionmentioning
confidence: 99%
“…16 The drop in Pt electrode potential was also observed by Takayama et al 18 For the oscillating chemiluminescence reactions, it was indicated that the superoxide anion O 2 ⋅ − promotes cycloaddition, followed by the detachment of nitrogen molecules that were incorporated into the phthalate dianion. 3,19 Previous theories 3,20 have suggested that intermittent intense fluorescence was due to the reaction of luminol with the hydroperoxyl radical HO 2 ⋅.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this reaction can generate luminescent spatiotemporal patterns of novel type (thermokinetic kinematic/phase waves) 17,18 . In further studies, we also proposed the stepwise reduction of the original kinetic mechanism to the core explaining only oscillations in terms of ten, 16 five, 19 and finally three dynamical variables, 20 composing the minimal oscillator, meaning that the latter mechanism cannot be further reduced to two variables without a loss of the oscillatory instabilities.…”
Section: Introductionmentioning
confidence: 98%
“…Jędrusiak et al. calculated the concentration of HO 2 Cu(OH) 2 − , − OS(O)CN, and HO 2 · 8 . Recently, Cervellati et al.…”
Section: Introductionmentioning
confidence: 99%